Student's Level of Understanding on Mobile Learning based Volcano Eruption. Issue 1 (November 2021) - Wardaya, N F; Pujianto,; Jumadi,
Abstract: This study aims to analyze student's level of understanding on mobile learning based volcano eruption. This research is quantitative descriptive. The sample were 200 students who lives in the area that affected by the eruption of Merapi Volcano (Magelang Regency, Sleman Regency, and Yogyakarta City), recruited using a simple random sampling. The instruments were online survey questionnaire of Student's Level of Understanding on Mobile Learning based Volcano Eruption. The distribution of the data is normal, reliable and homogen based the analysis used IBM SPSS Statistics 22 software. The results of this study indicate that students who lives in Merapi Volcano prone area have a good understanding about mobile learning based volcano eruption. Level of student's understanding on mobile learning meet a good criteria with percentage 72, 80%, level of student's understanding on volcano eruption meet a good criteria with percentage 73, 40%, and student's understanding on disaster mitigation meet a good criteria with higher percentage 76, 40%.